Pathologic basis of veterinary disease (Elsevier, 2017)
Diagnose and manage diseases using the newest information and research! 'Pathologic basis of veterinary disease', 6th Edition provides complete, illustrated coverage of both general pathology and the pathology of organ systems of domestic animals. Addressing species from dogs and cats to pigs and cattle - and many more - this reference describes the lesions and pathogeneses of diseases, how cells and tissues respond to injury, and the interplay of host defense mechanisms with microbes and injurious agents. Updates include the latest scientific advances and diagnostic information. Written by a team of expert contributors, this book includes an Expert Consult website with access to the complete digital book plus thousands of images and guidelines for sample acquisition and for performing a complete necropsy.